Land of Their Choice : The Immigrants Write Home - Blegen, Theodore Christian, 1891-1969 (Book collections on Project MUSE., 1955)
This collection of?American letters? that immigrants wrote to friends and relatives in the lands they had left tells a little-known human story that is part of the larger saga of America. It constitutes a kind of composite diary of everyday people at the.